COHESION IN THE STORY “ROBINSON CRUSOE” - Komang Astiari; I Wayan Budiarta (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
This study analyzed the use of cohesion, especially lexical cohesion in the story of “Robinson Crusoe”. Lexical cohesion has been crucial in the text since they bring continuity yet create a story that can be understood by the reader. This research is expected to contribute the development of linguistic studies and bring insights to those who intend to acquire knowledge in term of cohesion. The method applied in conducting this study was library research, whereas the data was taken from the story entitled “Robinson Crusoe” written by Daniel Defoew. The story was chosen since it is one of the well-known stories around the world that is enjoyable to read due to many factors and one of them is the usage of lexical cohesive devices that can bring continuity within the text.